[Habaradas, one of the ten Jose Rizal model students of the Philippines] - Habaradas, Ma. Araceli (Animo Repository, 1993)
SC President Ma. Araceli Habaradas was one of the ten Jose Rizal Model Students of the Philippines by the Order of the Knights of Rizal.